Synthesis and Properties of Silicon Carbide (Review) - Soltys, L.M.; Mironyuk, I.F.; Mykytyn, I.M.; Hnylytsia, I.D.; Turovska, L.V. (Physics and Chemistry of Solid State, 2023)
Silicon carbide is an extremely hard material that exhibits exceptional corrosion resistance as well as thermal shock resistance. Its high mechanical properties determine the increased performance of materials based on it. The combination of high thermal conductivity and low thermal expansion coefficient determines the stability of silicon carbide at high heating rates and under stationary thermal conditions. To date, significant progress has been made in the development of methods for the synthesis of various materials based on silicon carbide. The main synthesis methods that scientists use in their research are the sol-gel method, sintering, pyrolysis, microwave synthesis, chemical vapor deposition, etc. The use of "green" techniques in the synthesis of SiC has gained wide popularity due to environmental friendliness, renewability, and ease of implementation. This review analyzes modern research in the field of silicon carbide synthesis published in peer-reviewed professional journals.